Koniec (wielkiej) historii literatury narodowej. Od narracji nacjocentrycznej do małych kanonów - Mikołajec, Marek (Śląskie Studia Polonistyczne, 2014)
The author of the article poses a thesis on an end of the model of national literature, which dominated in the People’s Republic of Poland, and replacing narratives aimed at creating a stiff national discourse by the so-called “small canons” and “small narratives”. The article consists of a theoretical and a practical parts. In the first one, the author describes a shift from great narratives, consolidating a nation, to small narratives, supported by pan-national, humanistic, and comparative literary canons. In the practical part, Mikołajec interprets Ondraszek by Gustaw Morcinek, poems by Paweł Kubisz, and Pierwsza polka by Horst Bienek. He indicates that the foundation for opening a perspective of a new community in these books – an open community – is a paradoxical, universalist thinking, built upon Marxist and Hegelian understanding of history, and Christian ethics.